(untitled) (Journal of the College of Basic Education, 2022)
The research tagged ((Historian Ibn Abi Tai’ al-Halabi (575 AH - 630 AH 1179-1232 AD) a study of his biography and writings)) included several topics. Aleppo, and his father’s interest and care for him, being the only one who lived in the life of his father, who provided him with all the necessities of scientific and academic life.